What Options Do We Have? The Supply Chain Resilience Funnel - Kirstin Scholten; Dirk~Pieter van Donk; Stefania Boscari (Journal of Supply Chain Management, 2025)
Supply chain resilience (SCRes) enables an organization to deal with disruptive changes over time. Previous research has often examined SCRes as a standalone concept, overlooking its multidimensional and complex roots that enable organizations to deal with change. This research integrates SCRes with connectedness and potential. Together, these three dimensions determine the development of organizations in the adaptive cycle, conceptualized in panarchy theory. The research framework developed in this research combines well-known SCRes strategies with the idea of concurrent product, process, and supply chain (PPS) configuration. Analyzing in-depth, empirical data pertaining to 12 disruption processes experienced by seven organizations, this research develops the “supply chain resilience funnel.” The funnel depicts how organizations prepare SCRes practices across PPS configurations limited by their specific contextual characteristics (laws and regulations, market developments, business models, and choices). During the response stage, disruption characteristics (scope and scale) further reduce the available options. The SCRes funnel clarifies how an organization's PPS configuration shapes resilience, connectedness, and potential, as well as how these dimensions interrelate to deal with disruptive change over time.
Keywords: 330; adaptive cycle; panarchy theory; process; product; resilience; supply chain